Stigma to people living with HIV/AIDS in students of the Faculty of Dentistry of Universidad Nacional de Colombia: a useful reflection in dentistry and bioethics - John Harold Estrada Montoya; Andrés Leonardo Pantoja Neira; Luis Alberto Sánchez-Alfaro (Universidad Nacional de Colombia, 2014)
Stigma is an attribute that discredits, and ruins the identity of individuals. Currently, predominate erroneous and unfounded concepts generating negative attitudes and discriminatory, known as exerted stigma which promotes the construction of concepts and negative social meanings creating internalized stigma. Objective: to characterize the stigma among people living with HIV/AIDS (PLWHA) generated by students from the Faculty of Dentistry, Universidad Nacional de Colombia (FOUN). Materials and methods: Joint study yielded quantitative data and qualitative information from the subjectivities of the participants. A survey with 29 questions related to exert and internalized stigma was designed; it is innovated using the social network Facebook to implement. It involved 66 participants. Discussion and conclusion: in the surveyed students is present stigma to PLWHA. Needed intervention to abolish the misinformation and misconceptions against HIV/AIDS. Is proposed the bioethics to gestate a just society, to overcome social inequalities, stigma, discrimination, and to educate in parameters of respect and solidarity between human.